Analysis of Determinants of Fintech Adoption by MSMEs in Balikpapan City: DOI and TAM Approaches - Haripin Haripin; Susan Fatmawati (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study investigates how Diffusion of Innovation (DOI) factors shape perceived usefulness and ease of use in MSMEs’ fintech adoption, and how these perceptions influence behavioral intention and actual usage. Motivated by low digital literacy and uneven fintech adoption in Balikpapan, the study provides insights for stakeholders to enhance fintech utilization.. Methodology/approach: A quantitative survey was conducted targeting MSMEs in Balikpapan that are familiar with or have used fintech. Data were collected through online and offline questionnaires from 100 respondents and analyzed using SEM-PLS with SmartPLS 4.0. Results/findings: Six hypotheses were supported, while relative advantage ? perceived usefulness and complexity ? perceived ease of use were not significant. This suggests that MSMEs emphasize ease of use over perceived benefits. Accordingly, training, technical assistance, and more intuitive app designs are needed to strengthen effective adoption. Compatibility significantly improves perceived usefulness and ease of use, and observability enhances perceived usefulness, which in turn increases behavioral intention and actual usage. Conclusion: The integrated DOI–TAM model effectively explains fintech adoption among MSMEs in Balikpapan. Perceptual factors play a crucial role, while some DOI attributes do not significantly influence fintech perceptions.. Limitations: This study is limited to MSME fintech users in Balikpapan and uses a quantitative approach, which restricts deeper exploration of subjective motivations and user experiences. Contribution: The findings underscore the need for fintech solutions aligned with MSMEs’ digital literacy and operational needs. Strengthening government-led digital literacy initiatives and incorporating factors such as trust, perceived risk, and environmental influences is recommended for future research.